2010
DOI: 10.1007/s10815-010-9436-1
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and infertility

Abstract: Endometriosis is a debilitating condition characterized by high recurrence rates. The etiology and pathogenesis remain unclear. Typically, endometriosis causes pain and infertility, although 20-25% of patients are asymptomatic. The principal aims of therapy include relief of symptoms, resolution of existing endometriotic implants, and prevention of new foci of ectopic endometrial tissue. Current therapeutic approaches are far from being curative; they focus on managing the clinical symptoms of the disease rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
361
1
38

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(459 citation statements)
references
References 61 publications
8
361
1
38
Order By: Relevance
“…Medications, in particular nonsteroidal antiinflammatory drugs, may also play a role in infertility (17). Endometriosis was only reported in 10% of women with infertility, less than the rate expected in the general infertile population (25-50%) (18). While some prior studies have suggested an immunologic link between endometriosis and rheumatic disease, this is not supported by this study (19,20).…”
Section: Discussioncontrasting
confidence: 73%
“…Medications, in particular nonsteroidal antiinflammatory drugs, may also play a role in infertility (17). Endometriosis was only reported in 10% of women with infertility, less than the rate expected in the general infertile population (25-50%) (18). While some prior studies have suggested an immunologic link between endometriosis and rheumatic disease, this is not supported by this study (19,20).…”
Section: Discussioncontrasting
confidence: 73%
“…Many studies have declared that the etiology and pathogenesis of endometriosis still remain unclear [9,48]. The description of "intermediate stage" in the malignant transformation of "atypical endometriosis" [49], which today is classified by the degree of dysplastic histologic atypia [50] perhaps supports the hypothesis of "endometroid endometriosis" as related to the malignant transformation, and that the hypothesized endometroid endometriosis cells are the "atypical endometriosis."…”
Section: Consequences Of the Hypotheses And Discussionmentioning
confidence: 99%
“…However, the absence of reliable non-invasive marker for the diagnosis of endometriosis makes the true prevalence problematic. Endometriosis is primarily found in young menstruating women, rarely observed before puberty, after menopause or in women with amenorrhea but its occurrence is not related to ethnic or social group distinctions Journal Of Prevention & Infection Control [9]. Endometriosis is often associated with chronic fatigue, acute abdomen and with dyspareunia and dysmenorrhea [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Результаты многих исследований, сфокусиро-ванных на лечении эндометриоза, в зависимости от стадии противоречивы, даже при едином алгоритме лечения [23][24][25]. Очевидно, что пациентки с одина-ковой стадией заболевания, согласно классифика-ции ASRM, фактически несравнимы в проявлении симптомов и активности эндометриоза [7,26].…”
Section: результатыunclassified